2022
DOI: 10.5489/cuaj.8008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise on physical health status in bladder cancer patients

Abstract: Introduction: There is a scarcity of data on the impact of behavioral habits, such as exercise, on physical health in patients with bladder cancer. We investigated the association of exercise on self-reported physical health status and examined the prevalence of bladder cancer patients with sedentary lifestyle. Methods: We examined cross-sectional data of participants diagnosed with bladder cancer within the Behavioral Risk Factor Surveillance System (BRFSS) from 2016–2020. Patient health status was surveyed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Patients with bladder cancer are no exception and a recent study of 936 patients shows that one third self-reported a sedentary lifestyle and poor physical health (12). The study also concludes that implementation of exercise interventions could improve the health status of patients with bladder cancer and that clinicians should try to get patients engaged (12).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients with bladder cancer are no exception and a recent study of 936 patients shows that one third self-reported a sedentary lifestyle and poor physical health (12). The study also concludes that implementation of exercise interventions could improve the health status of patients with bladder cancer and that clinicians should try to get patients engaged (12).…”
Section: Introductionmentioning
confidence: 95%
“…However, there is evidence suggesting that patients with cancer are less likely to be physically active, or change their physical activity behaviour following diagnosis, calling for strategies to support physical activity in cancer survivors (11). Patients with bladder cancer are no exception and a recent study of 936 patients shows that one third self-reported a sedentary lifestyle and poor physical health (12). The study also concludes that implementation of exercise interventions could improve the health status of patients with bladder cancer and that clinicians should try to get patients engaged (12).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, physical activity/exercise was reported to significantly affect cancer prevention and progression, as it lowers both the incidence and recurrence of different tumor types [1][2][3][4][5][6]. Epidemiological studies show evidence of decreased risk of esophagus, stomach, colon, breast, endometrium, bladder, and kidney cancers in association with an active lifestyle, and a possible protective function against ovary, prostate, and pancreatic cancer (World Cancer Research Fund International, available at https://www.wcrf.org) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another variable to be taken into account in terms of health promotion is not only the absence of disease but also to promote adequate levels of self-perception of health and physical condition, as recommended by the WHO [ 24 ], which promotes studies that take into account not only objective measures of health but also subjective measures such as the self-perceptions mentioned above. These have been shown to be improved thanks to the regular practice of physical activity, favouring that these self-perceptions take on a positive meaning [ 25 ].…”
Section: Introductionmentioning
confidence: 99%